Perancangan Alat Pembelah Bambu - Wahyudhi Sutrisno; Rifandi Dwi Styawan; Benny Wibowo (Journal of Appropriate Technology for Community Services, 2021)
Kemiri Village has various kinds of livelihoods, one of which is a craftsman of besek weaving. Until now, besek craftsmen have only used traditional tools to split bambu into thinner strands. This takes a lot of time and effort in the process. Therefore it is necessary to innovate the bamboo splitting process by making a bambu splitting device for the bamboo splitting to run quickly so that the productivity of the besek woven craftsman can increase. The method of implementation consists of three stages used, the first stage is the design stage of the tool, the second stage is the stage of selecting materials and the last stage is the stage of making tools. Based on the simulation results of this bamboo splitter, the result is that this tool can split bambu into 8 thin bamboo sections Keyword: Kemiri Village, Besek, Craftsmen, Bamboo, Innovate